Effect of knowledge management on organizational performance of Central Statistics Agency (BPS) of Cilacap Regency - Muhammad Aldi; Linda Perdana Wanti (Syntax Corporation Indonesia, 2023)
The research objective is to analyze the effect of knowledge management on organizational performance. The research method uses descriptive quantitative methods, using questionnaires as the primary data collection tool. Many data analysis techniques use linear regression analysis. The results of this study indicate a significant positive relationship between knowledge management and organizational performance at BPS Cilacap Regency. It is proof that the implementation of knowledge management practices in the organization contributes significantly to the improvement of performance. The results of the analysis also show that aspects of knowledge management as structured knowledge, knowledge sharing, and the use of information technology have a positive impact on organizational performance.